AN ANALYSIS OF ENGLISH FOR PROFESSIONAL NURSES TEXTBOOK IN STIKES PEMKAB JOMBANG - Noviana, I'in; Rosmaharani, Shanti; Susilowati, Ari (STKIP PGRI Jombang, 2021)
An English textbook has an important role in teaching and learning process, to support the learning process in the classroom. The purpose of this study is to identify and analyze the English for Specific Purposes of Nursing bachelor program and diploma program. This study was conducted by using qualitative approach and analyses in descriptive method. The samples were 92 respondents and was divided from 62 students of 3rd grade of nursing bachelor program and 30 students of 3rd from diploma of nursing of STIKES Pemkab Jombang who are getting the English subject in this semester and the sampling technique used total sampling. The instrument of this study used questionnaire and the interview guideline in form of closed – ended question. The data analysis was descriptive analysis in the form of number. The result of this study revealed that the English for Nursing Textbook was well designed and encouraged the students’ ability to improve the skills in Nursing English language. English subject help the students to communicate in English to support their career in field of nursing Education. Although this english textbook is good enough, there are some evaluations, such as provided the listening comprehension for listening activity, so the lecturers have to open a youtube to improve the students’ ability in listening and speaking.